Testing the value of the postwar international order - Mazarr, Michael J. 1965- (Rand Corporation, 2018)
"Since 1945, the United States has pursued its interests through the creation and maintenance of international economic institutions, global organizations including the United Nations and G-7, bilateral and regional security organizations including alliances, and liberal political norms that collectively are often referred to as the "international order." In recent years, rising powers have begun to challenge aspects of this order. The purpose of this report is very specific: to evaluate the order's value -- to assess its role in promoting U.S. goals and interests, and to measure its possible economic benefits in a number of specific areas. To answer the question of the order's value, we first had to define the components of the order that we proposed to evaluate for possible value to U.S. interests. We then reviewed broad assessments of the order, as well as detailed empirical work on its specific components. The resulting analysis produced five major findings: the postwar order offers significant value to U.S. interests and objectives; specifically in quantifiable and return-on-investment terms, the order contributes to outcomes with measurable value and appears to have a strongly positive cost-benefit calculus; the postwar order represents a leading U.S. competitive advantage; if the United States wants to continue to lead globally, some form of order is vital; and a functioning multilateral order will be essential to deal with emerging security and economic issues."--Publisher's description
"Prepared for the Office of Net Assessment, Office of the Secretary of Defense."--Title page
Keywords: Internationale Organisation; Geopolitik; Weltordnung; USA; International organization; Liberalism; Security, International / 21st century; Geopolitics; World politics / 21st century